ANALISIS PENGARUH CURRENT RATIO, DEBT TO EQUITY RATIO, TOTAL ASSETS TURNOVER, NET PROFIT MARGIN TERHADAP RETURN ON EQUITY PADA PERUSAHAAN MANUFAKTUR DI BURSA EFEK INDONESIA PERIODE 2008-2010 - USWATUL KARIMAH (Program Studi Manajemen Universitas Muhammadiyah Gresik, 2018)
This research performed in order to test the influence of variabel, Current Ratio (CR), Debt to Equity Ratio (DER), Total Assets Turnover (TAT), dan Net Profit Margin (NPM) toward Return on Equity (ROE). Methodology research as the sample used proposive sampling with criteria as (1) Manufacturing companies that listing at JSX who provide financial report year ending 31st December during the observation period 2008 – 2010, well available at JASICA index. (2) Companies must be the listined at the beginning of the period of observation and not on the delisting until the end of the observation period. (3) The financial report include the value of financial ratios to be studied include ROE, CR, DER, TAT, and NPM. (4) At the beginning of the observation period until the end. Total of 23 samples obtained from 131 firms during the observation period of three years in the manufacturing sector. Sample amount as much 69 during the observation period of three years. Data analysis with multi linier regression of ordinary least square and hypotheses test used partial t - test, simultan F – test at level of significance 5%. Empirical evidence show as CR, DER, and TAT to have not significant influence toward ROE of manufacturing companies listing in JSX over period 2008 – 2010 at level of significance >5%. While the rest NPM to have significant influence toward ROE of manufacturing companies listined in JSX over period 2008 – 2010 at level of significance 5%. While, four independent variabel (CR, DER, TAT and NPM) to have significant influence toward ROE at level of significance 5% as 0,000%. Predictable of the four variables toward ROE is 56,9% as indicated by adjusted R square that is 56,9% while the rest 43,1% is affected by other factors is not included into the study model.